“A vida do crime é cruel”: uma análise dos sentidos da punição para adolescentes autores de atos infracionais - Andrade, Iraci Bárbara Vieira (2020)
This research aims to analyze the cycle of punishment for acts of infraction carried out by adolescents in Fortaleza, Brazil, by following the institutions these adolescents go through after their apprehension, which are: the Child and Adolescent Police Unit, the 1 st Infancy and Youth Court, the 5th Infancy and Youth Court, and finally the Dom Bosco Socio-Educational Center. The decision for a socio-educational measure in closed environment is predominantly based on the social imaginary that the internment of bodies and their exclusion from social life are the most effective ways of punishing criminals. For adolescents though, such measure should be only issued as an exception. However, this prerogative, ensured by the Child and Adolescent Statute, does not take place in Fortaleza, where Socio-Educational Centers operate in full capacity. In this perspective, I analyze not only the applicability of socio-educational measures in closed environment, but also how other instruments of punishment are enacted against the adolescent, ranging from physical violence to discourses reproduced by authorities, which demonstrate an attempt to morally reduce both youth and their families. The analysis of the cycle of punishment was conducted through an ethnographic incursion in the aforementioned institutions, where I sought to comprehend punishment in the perspective of adolescents, observing the relations that occurred in those sites. Interviews with adolescents and the narratives of their trajectories in crime were indispensable for the investigation, considering that punishment for them refers to the category pagar um vacilo (pay for messing up), and according to the logics of the groups they belong to, cobrar um vacilo (collect on messing up) is to punish. In other words, first we needed to understand how these adolescents dealt with punishment according to their own moral fluxes in order to apprehend its meaning for them. Therefore, it is possible to say these adolescents are not mere elementos, vagabundos e menores (perps, bums, minors) as they call themselves, but rather people permeated by moral fluxes that enact violence as a means for personal gains, as well as punishing other subjects as they break their own code value. Finally, I discuss the possibility of an adolescent to step out of a life of crime, especially those in the condition of batizados (baptized) in a criminal faction, and then lay out the opportunity of a bença (blessing) and the controversies around a real way-out of this “life”.